Analysis of Whole-Genome facilitates rapid and precise identification of fungal species - Qi, Guihong; Hao, Lijun; Xin, Tianyi; Gan, Yutong; Lou, Qian; Xu, Wenjie; Song, Jingyuan (Frontiers in Microbiology, 2024)
Fungal identification is a cornerstone of fungal research, yet traditional molecular methods struggle with rapid and accurate onsite identification, especially for closely related species. To tackle this challenge, we introduce a universal identification method called Analysis of whole-GEnome (AGE). AGE includes two key steps containing bioinformatics analysis and experimental practice. Bioinformatics analysis screens candidate target sequences named Targets within the genome of the fungal species and determines specific Targets by comparing with the genomes of other species. Then experimental practice using sequencing or non-sequencing technologies would confirm the results of bioinformatics analysis. Accordingly, AGE obtained more than 1,000,000 qualified Targets for each of 13 fungal species within the phyla Ascomycota and Basidiomycota. Next, sequencing and genome editing system validated the ultra-specific performance of the specific Targets, especially noteworthy is the first-time demonstration of the identification potential of sequences from unannotated genomic regions. Furthermore, by combining the rapid isothermal amplification and phosphorothioate modified primers with the option of instrument-free visual fluorescence method, AGE can achieve qualitative species identification within 30 minutes using a single tube test. More importantly, AGE holds significant potential in identifying closely related species and differentiating traditional Chinese medicines from their adulterants, especially in the precise detection of contaminants. In summary, AGE opens the door for the development of whole genome-based fungal species identification, also providing guidance for the application in plant and animal kingdoms.